Growth and nutrient absorption by Raisa tomato cultivar grown in hydroponic system - De Mello Prado, Renato [UNESP]; Santos, Victor Honorato Gonçalves [UNESP]; De Oliveira Gondim, Ancélio Ricardo [UNESP]; Alves, Adriana Ursulino [UNESP]; Filho, Arthur Bernardes Cecílio [UNESP]; Correia, Marcus André Ribeiro [UNESP] (Universidade Estadual de Londrina, 2011)
The production and quality of tomatoes has increased with the emergence of new genotypes and cropping systems such as hydroponics, however, there are few studies on the nutrition of plants. The objective was to evaluate the growth and motion of absorption of nutrients by Raisa tomato cultivar, grown in hydroponic system. The experimental design was randomized blocks with eight treatments consisting of the times of sampling: 15, 25, 35, 45, 55, 65, 75 and 85 days after transplanting (DAT) and five replications. The tomato seedlings were transplanted to pots of 8 dm3 (on 31-03-2008), filled with the base substrate of coconut fiber, constantly irrigated with Hoagland and Arnon nutrient solution. During the experimental period and focuses on the development of plants and dry leaves, stems, fruits and roots. The dry matter accumulation of leaves and roots of tomato cultivar Raisa was relativelyfaster than the national stem and fruit, over cultivation, with predominance of dry fruits (45%) on the leaves (27%), the stem (24%) and roots (3%) at the end of the cycle. The accumulation of nutrients and micronutrients by the tomato cultivar Raisa was fit with linear increase throughout the cultivation, except for Mn which was quadratic. Most of the tomato nutritional requirement for nutrients was K, N and Ca and micronutrients was Fe, Zn and Mn.
Crescimento e marcha de absorção de nutrientes em tomateiro cultivar Raísa cultivado em sistema hidropônico
Keywords: Development; Dry matter accumulation; Lycopersicon esculentum Mill; Plant nutrition